Ultrasensitive Detection of Proteins on Western Blots with Semiconducting Polymer Dots - Ye, Fangmao (2013)
We demonstrate ultrasensitive fluorescence imaging of proteins on Western blots using a bright, compact, and orange-emitting semiconducting polymer dot (CN-PPV). We achieved a detection limit at the single-picogram level in dot blots; with conventional Western blotting, we detected 50 pg of transferrin and trypsin inhibitor after SDS-PAGE and transfer onto a PVDF membrane. Our method does not require any additional equipment or time compared to the conventional procedure with traditional fluorescent probes.